2021
DOI: 10.1029/2020jc017158
|View full text |Cite
|
Sign up to set email alerts
|

Origin, Variability, and Pathways of East Sea Intermediate Water in a High‐Resolution Ocean Reanalysis

Abstract: The East Sea Intermediate Water (ESIW) of the East/Japan Sea (hereafter EJS) is a subsurface salinity minimum layer (<34.06 psu) with low temperature (1°C-5°C) and high dissolved oxygen content (>6.5 ml/l) (K. Kim & Chung, 1984;Y.-G. Kim & Kim, 1999). It is mainly found in the Ulleung Basin (hereafter UB), and to a lesser extent in the subpolar front region near 40°N (Figure 1). The water mass is formed south of Vladivostok as a result of active air-sea interaction during the East-Asia winter monsoon (Yoon & K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…The phytoplankton community of the EJS is characterized by the abundance and diversity of diatoms, dinoflagellates, and cyanobacteria (Choi et al, 2016). Diatoms are abundant in most of the regions, whereas the cyanobacteria abundance is comparatively high in the open waters (Kim S. Y. et al, 2021). Cyanobacteria occurs mainly in the surface mixed layer, whereas diatoms are dominant in the stratified zone at depths below 20 m (Kwak et al, 2017).…”
Section: Plankton Communitymentioning
confidence: 99%
See 1 more Smart Citation
“…The phytoplankton community of the EJS is characterized by the abundance and diversity of diatoms, dinoflagellates, and cyanobacteria (Choi et al, 2016). Diatoms are abundant in most of the regions, whereas the cyanobacteria abundance is comparatively high in the open waters (Kim S. Y. et al, 2021). Cyanobacteria occurs mainly in the surface mixed layer, whereas diatoms are dominant in the stratified zone at depths below 20 m (Kwak et al, 2017).…”
Section: Plankton Communitymentioning
confidence: 99%
“…Climate change affects hydrographic properties, water circulation, and, consequently, the biological and biogeochemical properties of the EJS (Chiba et al, 2008;Kim S. Y. et al, 2021). Joo et al (2016) Mass accumulation rate (colored circles; mg cm −2 yr −1 ) and SOC accumulation rate (values in brackets; molC cm −2 yr −1 ) in the EJS.…”
Section: Temporal Trendsmentioning
confidence: 99%
“…Ocean analysis data of water temperature (SST), salinity (SSS), and sea surface currents for June and July 2019 were provided by the Korea Institute of Ocean Science and Technology (KIOST) [9]. Since March 2017, KIOST has been operating the "Ocean Predictability Experiment for Marine environment (OPEM)", a real-time ocean circulation prediction system in order to detect oceanographic phenomena such as cold water zones and high temperatures occurring in the waters surrounding the Korean Peninsula.…”
Section: Remote Sensing Analysesmentioning
confidence: 99%
“…Data assimilation on the vertical structure of water temperature and salinity was performed once every 7 days with input data from Argo (https://data-argo.ifremer.fr/latest_data/, accessed on 5 June 2019) and in-situ data for temperature and salinity profiles provided by Global Temperature and Salinity Profile Programme (https://www.ncei.noaa.gov/data/oceans/gtspp/realtime/meds_ascii/, accessed on 5 June 2019). A previous study [9] presented the main information of the OPEM system and verification results such as water temperature and salinity in the waters surrounding the Korean Peninsula. Satellite-based Chl a observation data used daily Himawari-8 Level 3, and a geostationary orbit satellite operated by the Japanese Meteorological Agency, and the spatial resolution of the data is 1/20 • [14].…”
Section: Remote Sensing Analysesmentioning
confidence: 99%
“…Modeling studies also estimated the ventilation time of the ESIW to be 6-10 years from the point of view of particle dispersion (Seung and Kim, 1997;Yoshikawa et al, 1999), and this may be related to the problem in which the low-resolution numerical models of the past underestimated the mean and eddy circulation at mid and deep layers (Park and Kim, 2013). The latest model results suggested that the ESIW arrived at the Ulleung Basin in a relatively short time of 1-2 years (Kim et al, 2021), which is comparable to the results of this study, although there is still a significant difference from the observed results in terms of the ESIW formation area. Because the ESIW ventilation timescale is important information, a study reconciling the chemical tracer-based, numerical model-based, and physical observation-based timescales is required.…”
Section: Remaining Studies and Implicationsmentioning
confidence: 99%